Evaluation of intelligent road transportation systems : methods and results - Lu, Meng (The Institution of Engineering and Technology, 2016)
Intelligent Transport Systems (ITS) use information and communications technologies (ICT) to deliver transport improvements instead of extending physical infrastructure, thereby saving money and reducing environmental impact. This book provides an overview of ICT-based intelligent road transport systems with an emphasis on evaluation methods and recent evaluation results of ITS development and deployment. Topics covered include: ITS evaluation policy; frameworks and methods for ITS evaluation; ITS impact evaluation; the network perspective; field operational tests (FOTs); assessing transport measures using cost-benefit and multi-criteria analysis; technical assessment of the performance of in-vehicle systems; opportunities and challenges in the era of new pervasive technology; evaluation of automated driving functions; user-related evaluation of ADAS (Advanced Driver Assistance Systems) and automated driving; evaluation of traffic management; performance assessment of a wet weather pilot system; case studies from China; heavy vehicle overload control benefit and cost. With chapters from an international panel of leading experts, this book is essential reading for researchers and advanced students from academia, industry and government working in intelligent road transport systems.
Keywords: Intelligent transportation systems -- Evaluation.; Intelligent transportation systems.; Highway engineering.; elektronické knihy; electronic books